Effect of macromolecules on the viscosity of whole condensed milk - SAMPAIO, Aryele Nunes da Cruz Encide; CÉZAR, Camila koutsodontis Cerqueira; CARON, Evelyn Fernanda Flores; MORAES, Gustavo Nunes de; RAGHIANTE, Fernanda; POSSEBON, Fabio Sossai; PEREIRA, Juliano; MARTINS, Otávio Augusto (Food Science and Technology, 2024)
The viscosity of a fluid refers to the resistance to flow, such as in the case of whole condensed milk. Condensed milk is a product created by partially dehydrating milk, concentrated milk, or reconstituted milk, and then sugar is added. Its fat and protein content can be adjusted to meet specific characteristics. The aim of this study was to evaluate the effect of macromolecules on the viscosity of various brands of whole condensed milk. The brands of whole condensed milk analyzed were classified as LCA, LCB, LCC, LCD, and LCE, with a total of 50 samples from different batches. The viscosity was measured using the Ford cup method, which was validated through tests for linearity, detection limit, quantification limit, and repeatability. The physicochemical tests included viscosity, soluble solids (oBrix), moisture, protein, lipids, RMF, carbohydrates, total caloric value, and SNG. The main findings showed that the LCC, LCD, and LCE brands had high levels of macromolecules (protein, lipids, and carbohydrates) and viscosity. Consequently, it was concluded that high concentrations of macromolecules in whole condensed milk result in increased viscosity of the product.